MANAJEMEN LABA PADA PERIODASEBELUM DAN SESUDAH PENAWARAN SAHAM PERDANA DI BURSA EFEK JAKARTA: ANALISIS DENGAN MODEL DEANGELO - Elisa Indah; Erny Ekawati (Fakultas Bisnis UKDW, 2006)
The previous research fotmd empirical evidence about existence of earnings monagement of suuraunding IPO (Initial Public Offerings). Previous reseqrch also found that operating performance at period after IPO less than before IPO. The purposes of this research is to reexamine earnings management surrounding IPO and association earnings manog